Hsp90 in Cancer : Beyond the Usual Suspects - Isaacs, Jennifer (Professor of Pharmacology); Whitesell, Luke (Advances in cancer research, 2016)
This title focuses on the multifunctional molecular chaperone Hsp90 which regulates the post-translational stability and function of a broad repertoire of client proteins and discusses some of the lesser-known aspects of how Hsp90 and its related family members enable oncogenic transformation and malignant progression.